Nitrofurantoin Susceptibility Profile on Bacterial Isolates from Urinary Tract Infection in Patients with Diabetes Mellitus - Kurniawan, Prayoga; Mardhia, Mardhia; Mahyarudin, Mahyarudin (Muhammadiyah Medical Journal, 2023)
Background: Patients with diabetes mellitus have a higher risk of urinary tract infection (UTI) incidence than those without. One of the first-line therapy for UTI is nitrofurantoin. The emergence of drug-resistant UTIs is increasing both in community and healthcare setups. Purposes: Determine the nitrofurantoin susceptibility profile to bacteria causing UTI in diabetic patients. Method: A cross-sectional study was conducted at the Microscopic Laboratory, Faculty of Medicine, Universitas Tanjungpura, Pontianak, from February to November 2019. The antibiotic susceptibility testing was performed by the Kirby-Bauer disk diffusion method on 22 bacterial isolates. The samples were collected on a sterile urine pot, cultured on agar, and identified by biochemistry test, and bacterial isolates were stored at 2-8oC. The bacterial isolates were sub-cultured 24h before the susceptibility test. The susceptibility testing used a 300 µg nitrofurantoin disk. The diameter of zone inhibition was measured and classified based on Clinical and Laboratory Standard Institute guidelines. Result: The results showed that Escherichia coli was 41.67% susceptible (5/12), Shigella sp. was 100% intermediate (1/1), and Enterobacter aerogenes (3/3), Pseudomonas aeruginosa (1/1), Klebsiella sp (1/1) were 100% resistant. Conclusion: The majority of the causative bacteria for UTI in diabetic patients are resistant to nitrofurantoin, suggesting the use of nitrofurantoin should be reconsidered as an empirical antibiotic in Pontianak. Further study using a larger population should be conducted to describe a more extensive antibiotic susceptibility profile of diabetic patients with UTI in Pontianak.